Synthesis and evaluation of fluorimetric and colorimetric chemosensors for anions based on (oligo)thienyl-thiosemicarbazones - Santos-Figueroa, Luis E. (2012)
A family of heterocyclic thiosemicarbazone dyes (3a-d) containing thienyl groups has been synthesized, characterized and their chromo-fluorogenic response in acetonitrile in the presence of selected anions studied. Acetonitrile solutions of 3a-d show absorption bands in the 338-425 nm range which are modulated by the groups attached to the thiosemicarbazone moiety. The fluoride, chloride, bromide, iodide, dihydrogen phosphate, hydrogen sulfate, nitrate, acetate and anions were used in the recognition studies. Only sensing features were observed for fluoride, cyanide, acetate and dihydrogen phosphate anions. Two different chromogenic responses were found, (i) a small shift of the absorption band due to coordination of the anions with the thiourea protons and (ii) the appearance of a new red shifted band due to deprotonation of the receptor. For the latter process changes in the color solutions from pale-yellow to orange-red were observed. Fluorescence studies showed a different emission behavior according to the number of thienyl rings in the π-conjugated bridges. Stability constants for the two processes (complex formation + deprotonation) for receptors 3a-d in the presence of fluoride and acetate anions were determined from spectrophotometric titrations using the HypSpec program. The interaction of 3d with fluoride was also studied through 1H NMR titrations. Semiempirical calculations to evaluate the hydrogen-donating ability of the receptors were also performed.